Fine structure and isotope shift of tritium in the Balmer-α transition - Tate,DA; Baird,PEG; Boshier,MG; Hinds,EA; Stacey,DN; Woodgate,GK (Journal of Physics B Atomic Molecular and Optical Physics, 1988)
By means of saturated absorption spectroscopy in a discharge tube containing hydrogen isotopes, fine-structure intervals in the Balmer- alpha line of tritium have been measured, and for each of four components of that line the tritium-hydrogen and tritium-deuterium isotope shifts have been measured. The results agree with theory within the experimental limits of error, which are typically +or-2 MHz. The profiles of the components of Balmer- alpha have been analysed in detail and in particular a Stark-induced crossover signal has been revealed.